Ethical Principles As Student Motivation Continuing Education At Medical Faculty, Nahdlatul Ulama University, Surabaya - Sari, Paramita; Syarifah, Mustika Chasanatusy; Firdaus, Abraham Ahmad Ali (Jurnal Medis Islam Internasional, 2023)
Background : Ethics is an important component in human life to distinguish good and bad behavior. Motivation is very important when an individual wants to do something and decides something. Ethics supports a person's motivation to do things they think are good, including determining education at medical school. Objective : The research aims to find out students' thinking principles based on the science of ethics so that by knowing these thinking principles researchers can find out students' motivations in choosing and continuing their studies at medical faculty. Methods : This research is a quantitative study with a descriptive approach on all students of the Class of 2022 FK UNUSA. The survey used secondary data from student interviews from the new student admissions committee, data analysis using descriptive analytics and data validity using correlation tests. Result : The results of this research show that 81% of students have the principle of virtue ethic thinking, supported by Personal Characteristics Test data showing that 72% of students are advised to be accepted as students at the medical faculty. Conclusion : So, it can be concluded that virtue ethics is a motivation to continue education at the Faculty of Medicine, Nahdlatul Ulama University, Surabaya.